Synthesis and mesomorphic behavior of novel (bisthiophene)benzene carbazole nematic liquid crystals. Issue 1 (3rd July 2021) - Hu, Guang; Kitney, Stuart P.; Liu, Yanfang; Zhang, Kailong
Abstract: Two structural isomers of highly conjugated (bisthiophene)benzene carbazoles were designed and synthesized to study the effect of the substitution pattern on their liquid crystalline behavior, transition temperatures, energy levels, and band gaps. Unusually, only the isomer A with shorter terminal methyl chains exhibits a liquid crystalline phase, while the isomer B with longer octyl chains does not. It is because longer terminal octyl chains of isomer B strengthen not only the small angle between symmetrical sides of the aromatic backbone, but also the angle between the terminal alkyl chains and the aromatic backbone, thereby leading to a lower length-to-breadth ratio. Graphical abstract: UF0001